PELATIHAN KEWIRAUSAHAAN BAGI PELAKU UMKM USAHA KULINER PASAR LAMA DALAM MENINGKATKAN DAYA SAING BISNIS - Thio, Luky; Sesling (Publika Citra Media, 2024)
Along with efforts to increase product sales and income of typical food UMKM in the city of Tangerang an understanding of entrepreneurship is very necessary. This is a challenge for business people and UMKM which also acts as an opportunity. However, the abilities and skills of Indonesian UMKM are generally still low regarding entrepreneurial literacy. Education and training are crucial to increasing this understanding and skills and accelerating the economic growth of Indonesian UMKM. Specialty food UMKM in Tangerang City are very mushrooming considering the many types of nationally famous specialties, suchas laksa, nasi ulam, ginger chicken and its derivatives, various typical cakes, and so on. Entrepreneurship literacy education was carried out for several business people and UMKM operating in the specialty food sector in Tangerang City. Lectures and tutorials are the method of implementing the activity and are accompanied by door to door discussions at each business location of the training participants who previously registered their willingness to take part in this activity. The total number of participants was 15 business people and culinary and specialty food UMKM in Tangerang City. The results of this training and mentoring, apart from being able to increase entrepreneurial literacy, also motivate UMKM to continue to undergo digital transformation.